Associations between Dietary Fiber, the Fecal Microbiota and Estrogen Metabolism in Postmenopausal Women with Breast Cancer. (10th June 2021) - Zengul, Ayse G.; Demark-Wahnefried, Wendy; Barnes, Stephen; Morrow, Casey D.; Bertrand, Brenda; Berryhill, Taylor F.; Frugé, Andrew D.
Abstract: Breast cancer is a hormonally-driven cancer, and various dietary factors are associated with estrogen metabolism, including dietary fiber. Several studies report associations between dietary fiber and breast cancer; however, research on whether fiber influences circulating estrogens through the gut microbiota is rare. The objective of this cross-sectional study among 29 newly-diagnosed (stage 0-II), post-menopausal breast cancer patients is to examine associations between dietary fiber and the gut microbiota that are linked with β-glucuronidase activity, and purportedly increase circulating estrogens. Spearman's and partial correlations controlling for body mass index and age were performed using dietary recall data, Illumina MiSeq generated microbiota relative abundance, and HPLC-mass spectrometry-derived estradiol and estrone levels. Major findings are: (1 ) total dietary fiber is inversely associated with Clostridium hathewayi ( r= −0.419; p = 0.024 ); (2 ) soluble fiber is inversely associated with Clostridium (r=-0.11; p = 0.02); (3 ) insoluble fiber is positively associated with Bacteroides uniformis sp . ( r = 0.382; p = 0.041 ); and (4 ) serum estradiol and estrone levels are not correlated with species/genera or dietary fiber, though there is a trend toward an inverse association between soluble fiber and estradiol levels ( r= −0.30; p = 0.12 ). More studies are needed to understand the complex interaction between dietary fiber, intestinal microbiota, and hormonal levels in older females.